Strong In‐Plane Anisotropy and Giant Second Harmonic Generation Response of Organic Single‐Crystalline Microwire Arrays. Issue 18 (26th June 2022) - Guo, Yangwu; Zhao, Jinjin; Dong, Meiqiu; Yu, Ziwei; Fu, Yue; Feng, Jiangang; Gao, Hanfei; Wu, Yuchen; Jiang, Lei
Abstract: Organic nonlinear optical (NLO) crystals play an indispensable role in high‐performance photonic devices due to their large nonlinear coefficient, fast response time, and low dielectric constant. However, in contrast to the strides of bulk crystals, researches on the next generation of nanophotonic devices are ignored to some extent. One of the bottlenecks is the controllable manufacturing and patterning of high‐quality organic NLO crystals with the nanometer‐scale thickness. Herein, a confined assembly method for fabricating the microwire arrays of organic NLO crystal OH1 and DAT2 with precise position, flat morphology, high crystallinity, and consistent crystallographic orientation is reported. Two strong NLO effects observed in the experiments are comprehensively studied, including second harmonic generation (SHG) and two‐photon excited fluorescence. Furthermore, it is demonstrated that the anisotropic SHG effect depends on both the polarization of incident light and the crystallographic orientation of microwire arrays. Microwire arrays can exhibit large in‐plane anisotropy with the polarization ratio up to 0.95 and second‐order nonlinear coefficient up to 55.1 pm V −1 . This work provides new insights into the potential applications of organic NLO crystals in integrated optical devices. Abstract : Organic nonlinear optical (NLO) single‐crystalline microwire arrays of OH1 and DAT2 with precise position, flat morphology, and consistent crystallographic orientation are fabricated by a confined assembly method. Strong NLO effects observed in the experiments are comprehensively studied. Microwire arrays can exhibit large in‐plane anisotropy with the polarization ratio up to 0.95 and second‐order nonlinear coefficient up to 55.1 pm V −1 .